2013
DOI: 10.4028/www.scientific.net/amr.832.322
|View full text |Cite
|
Sign up to set email alerts
|

Evaporated Ethanol as Precursor for Carbon Nanotubes Synthesis

Abstract: Single-walled carbon nanotubes (SWCNT) were synthesized by using a simple evaporating method and a double furnace system. Ethanol was chosen as a carbon precursor because it has an evaporating temperature of 78 °C and was reported to produce a high purity of CNTs. Evaporated ethanol can be used as a precursor for carbon nanotubes (CNTs) synthesis. Ethanol was evaporated at 80 °C and channeled directly into a double furnace system. Furnace 1 was maintained at 180 °C and furnace 2 was set at 700 °C, 800 °C and 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The temperature of the small stainless tube is maintained at 180 °C. At this temperature, the solution of ferrocene and ethanol is ensured to vaporize properly . Once the CFs reach the reaction temperature, the needle valve is slowly opened to allow the vapor of the precursor to enter the chamber and come into contact with the surface of the fibers.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The temperature of the small stainless tube is maintained at 180 °C. At this temperature, the solution of ferrocene and ethanol is ensured to vaporize properly . Once the CFs reach the reaction temperature, the needle valve is slowly opened to allow the vapor of the precursor to enter the chamber and come into contact with the surface of the fibers.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Presently, there are controversial results regarding carbon nanomaterials toxicity, as some publication reported that carbon materials are toxic for neuronal-related cells. For instance, MWCNTs seem to inhibit neuronal differentiation of PC12 cells [123] and SH-SY5Y [124]. Moreover, Wu et al, [125] reported that exposure of DRG cultures to MWCNTs compromises regenerative axonogenesis [125].…”
Section: Accepted Manuscriptmentioning
confidence: 99%